Use of acetate for enrichment of electrochemically active microorganisms and their 16S rDNA analyses - Lee, JY; Phung, NT; Chang, IS; Kim, BH; Sung, HC (ELSEVIER SCIENCE BV, 2003)
A fuel cell-type electrochemical device has been used to enrich microbes oxidizing acetate with concomitant electricity generation without using an electron mediator from activated sludge. The device generated a stable current of around 5 mA with complete oxidation of 5 mM acetate at the hydraulic retention time of 2.5 h after 4 weeks of enrichment. Over 70% of electrons available from acetate oxidation was recovered as current. Carbon monoxide or hydrogen did not influence acetate oxidation or current generation from the microbial fuel cell (MFC). Denaturing gradient gel electrophoresis showed that DNA extracted from the acetate-enriched MFC had different 16S rDNA patterns from those of sludge or glucose+glutamate-enriched MFCs. Nearly complete 16S rDNA sequence analyses showed that diverse bacteria were enriched in the MFC fed with acetate. Electron microscopic observations showed biofilm developed on the electrode, but not microbial clumps observed in MFCs fed with complex fuel such as glucose and wastewater from a corn-processing factory. (C) 2003 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.
Keywords: MICROBIAL FUEL-CELL; BACTERIUM